2013
DOI: 10.1186/2228-5547-4-29
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using carob leaf extract and its antibacterial activity

Abstract: Investigations were carried out to compare the effectiveness of compounds such as sodium nitrite, trisodium citrate (TSC) and TSC-zinc acetate to inhibit the corrosion of steel rebar in simulated concrete interstitial solution contaminated with chloride and to explain the mechanism of corrosion inhibition on reinforcing steel by these systems. Inhibition efficiency of these systems was studied by electrochemical techniques such as potentiodynamic polarization and half cell potential measurements. Electronic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
208
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(238 citation statements)
references
References 46 publications
(29 reference statements)
29
208
0
1
Order By: Relevance
“…Thus, our result provides a promising spectroscopic signature of nanoparticle formation. The synthesis was evidently expressed by the bioreduction of silver ions into corresponding NPs which may be due to the presence of the nicotinamide adenine dinucleotide hydrogen-dependent enzyme, nitrate reductase that probably acts as an electron carrier in the reduction process [7]. The results of the present investigation revealed that several hydroquinones with redox potential in the microbial cells could also act as electron shuttle in the reduction mechanism and play a role in the formation of SNPs [17].…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Thus, our result provides a promising spectroscopic signature of nanoparticle formation. The synthesis was evidently expressed by the bioreduction of silver ions into corresponding NPs which may be due to the presence of the nicotinamide adenine dinucleotide hydrogen-dependent enzyme, nitrate reductase that probably acts as an electron carrier in the reduction process [7]. The results of the present investigation revealed that several hydroquinones with redox potential in the microbial cells could also act as electron shuttle in the reduction mechanism and play a role in the formation of SNPs [17].…”
Section: Resultsmentioning
confidence: 63%
“…Depending on their size shape and distribution they exhibit various properties. Different approaches have been used for the synthesis of NPs [7]. In recent past, a great deal of intensive effort has been put into the synthesis of NPs using plants and microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research in this field has reported the use of different plant leaf extracts for synthesizing silver nanoparticles, such as Gloriosa superba L. (47), Citrus limon L. (48), Carob (49) and Tephrosia purpurea L. (50). On the other hand, the synthesis of gold nanoparticles was reported using a tea leaf extract (51), Pelargonium graveolens (PeG) (52), Punica granatum (PuG) (53), Salvia offiinalis (SO) (54) and Morinda citrifolia roots extracts (55).…”
Section: Introductionmentioning
confidence: 99%
“…The biological route was chosen over common chemical and physical procedures because it is an easy, fast and eco-friendly option and does not involve any costly instrument or hazardous by-product as well (Awwad et al 2013). In recent times, plant-mediated (Banerjee et al 2014;Roy et al 2013;Phanjom et al 2012) and microbemediated (Sudha et al 2013;Malarkodi et al 2013;Honary et al 2013) synthesis procedures are frequently used for nanoparticle synthesis.…”
Section: Introductionmentioning
confidence: 99%